UNIVERSALITY IN MAGNETOEMISSION OF COMPACT ASTROPHYSICAL OBJECTS - Kondratyev, V. N.; Korovina, Yu. V.; Blanchard, Ph. (Одеські астрономічні публікації, 2016)
Magnetodynamics of inhomogeneous crusty nuclear matter is considered accounting for quantum fluctuations and ferromagnetic coupling. We show that anomalies in nuclide magnetic moments give rise to erratic jumps in magnetotransport of neutron star crusts. Universal properties of such a noise are favorably compared with statistical and temporal features of Soft Gamma Repeating bursts.